Energy performance comparison among see-through amorphous-silicon PV (photovoltaic) glazings and traditional glazings under different architectural conditions in China. (1st April 2015) - Liao, Wei; Xu, Shen
Abstract: With the emergence and rapid deployment of PV (photovoltaic) façades, a comparison among see-through amorphous silicon (a-Si) PV glazings and traditional glazings under different architectural conditions could provide us a broader perspective for comprehending the energy performance and utilisation of see-through a-Si PV glazing in BIPV (building integrated photovoltaic) applications. In this paper, two see-through a-Si PV glazings of different transmittance are investigated and compared with three traditional glazings in terms of PV electricity generation and energy consumption during lighting, cooling, and heating in China. The impacts of the architectural conditions are considered in the study, particularly with respect to five factors: room depth, room height, room width, window height, and WWR (window-to-wall ratio). A calculation model for a see-through a-Si PV glazing is developed and validated with field experiments to perform simulations using Energy Plus. The results indicate that see-through a-Si PV glazings have great potential and exhibit better energy performance than single and double glazings, where cooling energy consumption is the dominant factor. The results also suggest that see-through a-Si PV glazings are more beneficial than traditional glazings when they are applied in shallow rooms with large windows or high ceilings. Highlights: Energy performance comparison between a-Si see-through PV and traditional glazings. A-Si PV; superior to single and double glazings, inferior to low-E glazings. Savings from reduced cooling energy consumption is the main contributing factor. A-Si PV; more beneficial in shallow rooms with large windows/a large room height.